2013
DOI: 10.7150/jca.5835
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Infectious Agents in Colorectal Cancer Development

Abstract: Colorectal cancer (CRC) is a major burden to healthcare systems worldwide accounting for approximately one million of new cancer cases worldwide. Even though, CRC mortality has decreased over the last 20 years, it remains the third most common cause of cancer-related mortality, accounting for approximately 600,000 deaths in 2008 worldwide. A multitude of risk factors have been linked to CRC, including hereditary factors, environmental factors and inflammatory syndromes affecting the gastrointestinal tract. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 88 publications
(91 reference statements)
0
64
0
Order By: Relevance
“…Colorectal cancer is one of the most common types of cancer worldwide (1). Sporadic occurrence and heterogenetic nature of colorectal cancer, including many factors, may be involved in colorectal cancer (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colorectal cancer is one of the most common types of cancer worldwide (1). Sporadic occurrence and heterogenetic nature of colorectal cancer, including many factors, may be involved in colorectal cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, colorectal cancer is one of the main problems for healthcare systems, accounting for approximately one million of new cases yearly (1). Epidemiological studies have shown that colorectal cancer is the fourth most common cancer in Iran (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CRC mortality has decreased over the last 20 years, it remains the third most common cause of cancer-associated mortality, accounting for ~600,000 fatalities in 2008 worldwide (1). Therefore, identification of tumor biomarkers for screening and early detection is imperative for patients with colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a major burden to healthcare systems worldwide, accounting for approximately one million novel cancer cases (1). Although CRC mortality has decreased over the last 20 years, it remains the third most common cause of cancer-associated mortality, accounting for ~600,000 fatalities in 2008 worldwide (1).…”
Section: Introductionmentioning
confidence: 99%